Living Water: a look at sufficiency in Cameroon - Blick Bassy (Field Actions Science Reports)
In this interview Blick Bassy, a long-term campaigner for the preservation of water resources, talks about his vision of sufficiency. Many people in Cameroon who live without permanent access to tap-water intuitively manage water resources frugally. Their approach is rooted in a more direct relationship to water which, being visible, is almost a living thing. But in Cameroon and other African countries, water plays a vital spiritual and cultural role too. Ultimately, raising awareness about the scarcity of water resources can be achieved not only by focusing on water’s universal character as a common foundation for all, but also by using the art of music to shape new perceptions about water, as demonstrated by Blick Bassy.